CONSIDERATIONS FOR E-FORENSICS: INSIGHTS INTO IMPLICATIONS OF UNCOORDINATED TECHNICAL, ORGANISATIONAL AND LEGAL RESPONSES TO ILLEGAL OR INAPPROPRIATE ON-LINE BEHAVIOURS - Broucek, Vlasti; Turner, Paul (International Journal of Computing, 2014)
The growing incidence of e-crime and computer misuse has increased demand for effective defensive and offensive solutions. Most responses have tended to focus on discrete sets of technical, organisational or legal challenges, but there is increasing recognition of the need for more integrated solutions that balance security, individual privacy and the generation of legally admissible digital evidence. More importantly, there is also proof to indicate that these fragmented approaches are impairing their own effectiveness due to the inter-relatedness of challenges faced. This research paper adopts an e-forensic approach to examine the links between technical, organisational and legal responses to the challenges posed by illegal or inappropriate on-line behaviour. The paper acknowledges some of the numerous challenges that remain unresolved in each approach and argues that future developments must be focused on integrated and balanced solutions that are calibrated to address the dynamic and multi-faceted nature of the forensic computing domain.